Adenomatoid tumorof epididymis: An unusual cause of scrotal swelling - Pai, Narendra; Hegde, Suraj; Cherukumudi, Amulya; TP, Rajeev (Indian Journal of Case Reports, 2020)
Adenomatoid tumor of the epididymis is a rare yet benign lesion, which is believed to take its origin from mesothelial cells. These are small in size, are incidentally detected on clinical examination, and are seldom associated with pain. These indolent tumors have no malignant potential, but can invade the testicular parenchyma, and thereby raising the suspicion of a malignant testicular lesion. Here, we present a case of a 36-year-old male with a left hemi-scrotum swelling for 2 months, which was non-progressive and it was not associated with pain. On palpation, there was a hard, solitary swelling overlying the left testis, which was suspicious of malignancy. The patient then underwent a testicular sparing excision of the left epididymal mass. It is critical to identify such lesions preoperatively to avoid unnecessary orchidectomy and stress to the patient.